Discriminating Cells by Membrane Surface Charge May Improve Long-Term Refrigerated Storage of Red Blood Cells - Liadov, Daniil; Berest, Volodymyr (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):287